God, Time, and the Implicate Order Theory - Korpela, Sampsa (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
In this article, the God’s relationship to time is viewed from the perspective of modern physics. The purpose is to examine new perspectives by introducing a theory of time that has been unexplored in contemporary theology. The paper begins with an analysis of the two competing views of God’s relationship to time: timelessness and temporality. They are reviewed from the perspective of the special theory of relativity. In contemporary theology, God’s timelessness is usually combined with the block universe theory, which is based on the concept of unchanging spacetime. God’s temporality is usually associated with presentism, which denies the concept of spacetime. This division reflects a central conflict in physics: the mainstream interpretation of the special theory of relativity treats time as unchanging spacetime, while quantum physics treats time as dynamic and flowing. To resolve this conflict between the ontologies of the special theory of relativity and quantum physics, the implicate order theory is introduced. The implicate order theory was developed by David Bohm (1917–1992), one of the most visionary physicists of the 20th century. After introducing the theory, it is applied to the context of God’s relationship to time. This produces interesting new opportunities for theological research.